A high-valence bismuth(V) nanoplatform triggers cancer cell death and anti-tumor immune responses with exogenous excitation-free endogenous H2O2- and O2-independent ROS generation - Yizhang Tang; Xujiang Yu; Liangrui He; Meng Tang; Wenji Yue; Ruitong Chen; Jie Zhao; Qi Pan; Wanwan Li (Nature Communications)
Abstract Reactive oxygen species with evoked immunotherapy holds tremendous promise for cancer treatment but has limitations due to its dependence on exogenous excitation and/or endogenous H2O2 and O2. Here we report a versatile oxidizing pentavalent bismuth(V) nanoplatform (NaBiVO3-PEG) can generate reactive oxygen species in an excitation-free and H2O2- and O2-independent manner. Upon exposure to the tumor microenvironment, NaBiVO3-PEG undergoes continuous H+-accelerated hydrolysis with •OH and 1O2 generation through electron transfer-mediated BiV-to-BiIII conversion and lattice oxygen transformation. The simultaneous release of sodium counterions after endocytosis triggers caspase-1-mediated pyroptosis. NaBiVO3-PEG intratumorally administered initiates robust therapeutic efficacies against both primary and distant tumors and activates systemic immune responses to combat tumor metastasis. NaBiVO3-PEG intravenously administered can efficiently accumulate at the tumor site for further real-time computed tomography monitoring, immunotherapy, or alternative synergistic immune-radiotherapy. Overall, this work offers a nanomedicine based on high-valence bismuth(V) nanoplatform and underscores its great potential for cancer immunotherapy.